THE IMPACT OF THE SIMON SAYS GAME ON ATTENTION AND LISTENING SKILLS IN IRAQI PRIMARY SCHOOL STUDENTS: A PILOT STUDY - Salih, Balsam Hussein (PT. Antis International Publisher, 2025)
Objective: This pilot study investigated the impact of the Simon Says game on attention and listening skills among 16 males from Al-Moallem Elementary School, students aged 8–9 years in Diyala, Iraq. Method: The study employs a pre-experimental design to measure changes in attention and listening skills before and after a four-week treatment period. Participants engaged in the Simon Says game for 20 minutes daily, four times a week. Attention and listening skills were assessed using a standardized test adapted from the Test of Everyday Attention for Children (TEA-Ch), and teacher observations were recorded using a structured checklist. Results: Results from paired t-tests revealed statistically significant improvements in both attention (pretest M = 12.31, posttest M = 15.44, p < 0.001) and listening skills (pretest M = 10.25, posttest M = 13.69, p < 0.001). Teacher observations further supported these findings, noting improved focus, reduced impulsivity, and increased participant engagement. Novelty: The study concludes that the Simon Says game is a low-cost, scalable intervention that can potentially enhance cognitive and behavioral outcomes in resource-limited settings. However, the small sample size and lack of a control group limit the generalizability of the findings. Future research should include larger, more diverse samples and a control group to validate these results.